Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1080/0141192870130304
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Processes in Social Studies Classrooms and Prescriptive Instructional Theories

Abstract: An exploratory study of teaching styles in 40 social studies classrooms was described. Observational data were cluster‐analysed and three teaching styles were described. It was found that inexperienced teachers favoured an informational teaching style. The implications of the study for the possible empirical testing of prescriptive, instructional theories were discussed, and it was suggested that sufficient variance of teaching style could be found in natural, intact classrooms to justify optimism about the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Most of the Asian students had been tutor-oriented learners (Zhan, 1995) while they were learning in their native countries. Their original learning process was described by Hacker and Carter (1987) as a kind of knowledge transmission, but they tended to become peer-oriented learners when they studied abroad (Chalmers & Volet, 1997). Because Asian adult learners have had more opportunities to undertake e-mail interactive learning overseas than they had in their own countries, this has made them more likely to accept this new learning approach.…”
Section: Tutor-oriented Vs Peer-orientedmentioning
confidence: 99%
“…Most of the Asian students had been tutor-oriented learners (Zhan, 1995) while they were learning in their native countries. Their original learning process was described by Hacker and Carter (1987) as a kind of knowledge transmission, but they tended to become peer-oriented learners when they studied abroad (Chalmers & Volet, 1997). Because Asian adult learners have had more opportunities to undertake e-mail interactive learning overseas than they had in their own countries, this has made them more likely to accept this new learning approach.…”
Section: Tutor-oriented Vs Peer-orientedmentioning
confidence: 99%
“…Each updated Similarity Matrix and group membership is returned to the clustering procedure which ceases when only two groups remain. The pattern is represented as a dendrogram and a section of this, for the sample studied (n=40) (Hacker and Carter, 1987), is illustrated in Figure 2. Everitt (1980: 75) draws attention to validity issues and notes that several intuitively reasonable methods for validating clusters have been suggested.…”
Section: Using Shufter -A Fortran IV Clustering Algorithmmentioning
confidence: 99%
“…As a consequence, a high degree of confidence can be placed on the natural grouping of the three clusters which emerged to form a typology of social studies teaching styles. The three approaches to teaching social studies, identified above, were resolved from this analysis and are characterised in terms of pen-portraits elsewhere (Hacker and Carter, 1987).…”
Section: Using Shufter -A Fortran IV Clustering Algorithmmentioning
confidence: 99%
See 2 more Smart Citations